Acute Biliary-Pancreatitis: is early Cholecystectomy Safe? - Mohammad Hassan Abbas, Noor Ahmed Niazi, Mohtmam Nazir, Haroon-Ur-Rashid, Sultan Ahmed Awaisi, Sajid Anwer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the relationship between socio-demographic, intrapersonal factors and patient delay among breast cancer cases. Method: It was a cross-sectional study conducted in three divisions of Punjab province i.e. Lahore, Faisalabad and Multan. A total of 350 breast cancer patients who were under treatment in the public sector hospitals participated in the study. The respondents were selected through multistage sampling technique and responses were taken through the intrapersonal scale of breast cancer patients developed by the researcher. Results: Under socio-demographic antecedents, income, education, and distance were associated with the patient delay. Poor awareness of the disease was found among respondents, about 40% of the respondents were unaware of its signs and symptoms. A majority of the respondents (45.6% ) did not share the basic signs and symptoms of the disease with family members due to shyness. The traditional mode of treatment was preferred by more than 50% of the respondents (SA=29.1%, 22.6 A=). A significant relationship was also found between intrapersonal factors and the patient delay. Conclusion: The socio-demographic factors were found to be important determinants of the patient delay among breast cancer patients. Intrapersonal factors including less knowledge and awareness, fear of disease, shyness, and belief in spiritual healing and alternative medicine were negatively affecting the timely presentation of patients to the doctors. So, there is a need to launch effective awareness programs based on the socio-demographic characteristics and individual circumstances of the patients.